(untitled) (Research, Society and Development, 2024)
Introduction: Leishmaniasis is an endemic protozoan parasitic infection. Cutaneous leishmaniasis is the most prevalent subtype in Latin America. It is estimated that approximately 1 million new cases are diagnosed annually. The pathology is initially characterized by a papule at the site of the insect bite that grows until it forms an ulcerated lesion. Method: Literature review with searches in the Scielo and PubMed databases, inclusion and exclusion criteria were applied, resulting in 24 articles, all discussed here. Results and Discussion: First-line therapy consists of the use of systemic antimoniates; however, many patients present side effects to the treatment, requiring discontinuation of use. Thus, in search of a therapeutic alternative, the use of intralesional antimoniate has shown to have similar efficacy to systemic treatment, being indicated for patients with few lesions, with a size smaller than 3 cm in diameter. Studies indicate that the use of intralesional antimoniate has few or no adverse effects, leading to initial and definitive cure in more than 50% of patients. In addition to proven efficacy, studies indicate other advantages of intralesional applications, such as: lower doses of antimony, flexible therapeutic schedule and more spaced applications. Conclusion: Intralesional antimoniate therapy presents satisfactory results, with high cure rates and few adverse effects. Global medical protocols are recommended.